New Recreational Water Quality Criteria and Their Impact on Beach Advisories in Coastal Georgia - Asli Aslan; Sara Benevente (Georgia Southern University, 2016)
Background: To monitor pollution of marine beaches in Georgia, enterococci have been used as indicators of fecal contamination. For the 1986 Recreational Water Quality Criteria (RWQC), the beach action value (BAV) was 104 colonyforming units (CFU)/100 ml; the new RWQC, instituted in 2012, is 70 CFU/mL, a 32.6% decrease. When the beach action value is reached, authorities are to issue a beach advisory for protection of swimmer health. The present study investigated changes in compliance with the 2012 RWQC at five high-use beaches in Georgia. Methods: In the summer of 2015, samples of water were collected from five beaches at Tybee Island. Enterococci concentrations were enumerated by USEPA-approved methods. Samples exceeding the 1986 and 2012 RWQC beach action values were compared with times that advisories were posted at these beaches. Results: At these beaches, advisories were posted four times during the summer. Since, in 2015, the previous RWQC was in use, these decisions were based on the guideline value of 104 colon-forming units (CFU)/100 ml. When the new beach action value (70 CFU/100 ml) was applied, retrospectively, for samples collected at these sites, we found that the number of advisories would have been doubled if this value had been in place at that time. Conclusions: Staring from January 2016, Georgia has adopted new water quality criteria to monitor beaches. Decreasing the beach action value to 70 CFU/100 ml strengthens beach monitoring programs because it allows for better prevention from waterborne diseases, thus protecting the health of swimmers.